2008
DOI: 10.1590/s1415-790x2008000300012
|View full text |Cite
|
Sign up to set email alerts
|

Excesso de peso e hipertensão arterial em trabalhadores de empresas beneficiadas pelo Programa de Alimentação do Trabalhador (PAT)

Abstract: OBJETIVO: Avaliar as prevalências de excesso de peso (EP), hipertensão arterial (HA) e fatores associados em trabalhadores de empresas beneficiadas pelo Programa de Alimentação do Trabalhador (PAT) da cidade de São Paulo. MÉTODOS: Estudo transversal com 1.339 trabalhadores de 30 empresas. A coleta de dados envolveu a aplicação de um questionário com dados de caracterização dos trabalhadores e peso e altura auto-referidos. Foi realizada a aferição da pressão arterial e o estado nutricional foi classificado segu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
23

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 18 publications
0
14
0
23
Order By: Relevance
“…A study with individuals with HIV/AIDS and patients with angina pectoris 19 The high prevalence of overweightness (overweightness/ obesity) (52.7%) in this population of hypertensive patients with HIV/AIDS is in line with the alarming rates of overweightness described in the literature, which showed the prevalence of 53.7 to 58% of individuals with BMI above 25 in different populations 21,22 . Among Brazilian workers, there was high prevalence of overweightness (approximately 46%) and SAH (approximately 30%), mainly among males 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A study with individuals with HIV/AIDS and patients with angina pectoris 19 The high prevalence of overweightness (overweightness/ obesity) (52.7%) in this population of hypertensive patients with HIV/AIDS is in line with the alarming rates of overweightness described in the literature, which showed the prevalence of 53.7 to 58% of individuals with BMI above 25 in different populations 21,22 . Among Brazilian workers, there was high prevalence of overweightness (approximately 46%) and SAH (approximately 30%), mainly among males 23 .…”
Section: Discussionmentioning
confidence: 99%
“…O Programa de Alimentação do Trabalhador (PAT), criado, em 1976, com o intuito de melhorar as condições nutricionais de trabalhadores de baixa renda, atendia, em fevereiro de 2011, mais de 13 milhões de trabalhadores 4 . Porém, em cerca de 30 anos de sua existência, estudos têm apontado a oferta de refeições inadequadas do ponto de vista nutricional 5,6 e a manutenção e/ou ganho de peso excessivo por parte dos beneficiados 5,[7][8][9] .…”
Section: N T R O D U ç ã Ounclassified
“…It demonstrated that, although it was known as a state activity mainly aimed at the workers' health, the Tax Incentive Program for Workers' Food (Programa de Incentivo Fiscal à Alimentação do Trabalhador; PIFAT/PAT), instituted in 1976, was explicitly and essentially Tax Incentive Legislation for businesses. These two words (tax and food) allowed it to be characterized not only as a Workers' Food Program (PAT) 22,23,24 , but also as a program for tax and food simultaneously (PIFAT/PAT), a real combination concealed by the amnesia of genesis but revealed by this investigation. In its formulation and management, it was constituted as a social space of relationships between agents from different social fields, predominantly from economics, while nutritional health professionals played a secondary role.…”
Section: Introductionmentioning
confidence: 85%
“…While some works simply reproduce the content of norms and documents, uncritically accepting the official discourse 23,31 , others have explicitly or implicitly considered two conceptions of the State in their analyses: the classical view, which operates through PAT for the wellbeing of workers 24,32,33 and the Marxist concept, in which the State's function is to reproducte the workforce and to mitigate capital-labour conflicts 27,34 .…”
Section: Introductionmentioning
confidence: 99%